Record linkage for drug monitoring. - Skegg, D C (1981)
A study was carried out to assess the feasibility of using record linkage for drug monitoring. For two years, three types of records were collected for a total of 43 117 people: (1) details of basic attributes, such as sex and age; (2) details of prescriptions dispensed; and (3) records of hospital admissions, obstetric deliveries, and deaths. The records about each person were linked together, and analyses were performed to reveal associations between drugs and diagnoses. The study suggested that record linkage would be useful both for generating and for testing hypotheses about the adverse effects of drugs. The method would be especially valuable for detection of delayed effects (such as the induction of cancer), sudden deaths outside hospital, and effects of the fetus-all of which are difficult to study by other means. A full-scale project would need to cover a large population, and some of the practical issues that would arise are discussed.